Future of e-Banking in India— An Empirical Study of Employee’s Perceptions - Uppal, R. K (Journal of Commerce and Trade, 2011)
The paper is an attempt to study the perceptions of employee’s regarding e-banking services and their future in India. On the basis of five-point likert-type scale, this paper concludes that the employees are satisfied with the working of e-channels and they are agree to use the e-channels but not much satisfied with the knowledge management and behavioral aspects of e-banking. The employees experienced some frustration and a major problem of lack of knowledge of e-channels and their operating ways while dealing with these channels are the most prevalent ones. Keywords: E-Channels, Employee’s Perceptions.